Bimbingan Kelompok Berbantuan Al-qur’an: Sebuah Solusi Peningkatan Kecerdasan Emosi Mahasiswa Bimbingan dan Penyuluhan Islam - Jannati, Zhila; Indri M., Dwi Bhakti (Bulletin of Counseling and Psychotherapy, 2019)
Someone will be able to face various challenges in daily life if emotional intelligence is well developed. This study aims to find out how the psychoeducational group assisted with Al-quran can be a solution to improve student emotional intelligence. This research was used qualitative research method with 8 participants of Islamic Guidance and Counseling departement of Islamic State University (UIN) Raden Fatah Palembang. The results of this study indicate that emotional intelligence of students, which includes recognizing self-emotion, managing emotions, motivating oneself, recognizing the emotions of others, and building relationships, can be improved by giving psychoeducational group assisted with Al-qur'an. From the results of these studies it can be concluded that the psychoeducational group assisted with Al-qur'an can be a solution to improve student emotional intelligence.